(untitled) (مجلة الفاروق للعلوم, 2026)
Hepatocellular carcinoma (HCC) is one of the most important challenges in global oncology with profound metabolic derangements, specific enzymatic modifications and systemic homeostatic changes. Clinical laboratory surveillance of hematological baseline parameters is an important non-invasive diagnostic tool to monitor cellular cytotoxicity, to assess the physiological course of malignancy and to identify secondary systemic stress before clinical manifestation. Objectives: The aim of this study was to determine the prevalence of Hepatocellular Carcinoma, and evaluate hematological changes associated with the clinical progression of hepatocellular carcinoma. The clinical effect of age and gender on the major laboratory profiles was specifically studied. Methodology: A cross-sectional laboratory-based study was conducted over a period of four months (February-May 2026). Clinical and laboratory data sets were assembled based on confirmed cases of HCC from large regional oncology centers. Statistical analysis was carried out using descriptive indices, independent t-test and effect size (Cohen’s d) calculations with SPSS. Results: The epidemiological indicators showed a significant vulnerability in advanced age, the critical mass of cases (96.25%) being concentrated in cohorts over forty years, with a predominance of men (60%). Hematologic assessment showed a unique inflammatory and defensive response with a rapid increase in the counts of White Blood Cells (WBC) and Platelets (PLTs), with red blood cell indices (RBCs and MCH) temporarily within the normal range. Conclusion: The epidemiological indicators of this study established a robust correlation between advanced age and the clinical manifestation of hepatocellular carcinoma, with the critical mass of cases (96.25%) concentrated in patient cohorts exceeding forty years of age, Furthermore, a pronounced gender disparity was recorded in favor of males (60%). The secondary inflammatory hematological changes caused by progression of HCC. This underscores the clinical need for multi-parametric diagnostic surveillance, as isolated use of baseline laboratory profiles without radiological correlation can lead to misleading clinical interpretation delaying prognosis.